2004
DOI: 10.1158/0008-5472.can-04-1117
|View full text |Cite
|
Sign up to set email alerts
|

α2HS-glycoprotein, an Antagonist of Transforming Growth Factor β In vivo , Inhibits Intestinal Tumor Progression

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 47 publications
(57 reference statements)
5
74
0
Order By: Relevance
“…This is an important indicator that AHSG is involved in the insulin signaling pathway. Furthermore, it appears to boost the likelihood of developing gestational diabetes during pregnancy (Srinivas et al, 1993;Kalabay et al, 2002;Swallow et al, 2004;Stefan et al, 2006;Briana et al, 2008). In fact, our results show that serum AHSG levels were increased in the PE group as determined by both the SRM assay ( Figure 3) and ELISA assay (Figure 4).…”
Section: Resultsmentioning
confidence: 61%
“…This is an important indicator that AHSG is involved in the insulin signaling pathway. Furthermore, it appears to boost the likelihood of developing gestational diabetes during pregnancy (Srinivas et al, 1993;Kalabay et al, 2002;Swallow et al, 2004;Stefan et al, 2006;Briana et al, 2008). In fact, our results show that serum AHSG levels were increased in the PE group as determined by both the SRM assay ( Figure 3) and ELISA assay (Figure 4).…”
Section: Resultsmentioning
confidence: 61%
“…Alpha-2-HS glycoprotein (AHSG), is a glycoprotein present in the serum, is synthesised by hepatocytes and is important in blocking transforming growth factor-beta1 signal transduction, which is associated with tumour progression. AHSG has been observed to be depleted in certain tumours compared with normal tissue [19,20]. Kawakami et al [21] reported that AHSG was differentially expressed in the sera of hepatocellular carcinoma (HCC) patients who had undergone curative radiofrequency ablation treatment and may be a candidate biomarker for the development of diagnostic and therapeutic tools.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Fetuin-A has been shown to block TGF-␤1 binding to the extracellular motifs of TGF-␤II receptor, suppressing TGF-␤ signaling and inhibiting TGF-␤ induced epithelial-mesenchymal transition. 4 TGF-␤ inhibits normal epithelial cell proliferation, 25 but in many human cancers, TGF-␤ expression is elevated. 26 To determine whether fetuin-A modulates TGF-␤ signaling during mammary carcinogenesis, we probed mammary tissue sections of PyMT/Fet Ϫ/Ϫ and PyMT/Fet ϩ/ϩ mice with antiphospho-Smad2/3 (P-Smad2/3), a downstream target of TGF-␤ as a readout.…”
Section: Fetuin-a Attenuates Tgf-␤ Signaling In Normal Mammary Epithementioning
confidence: 99%
“…[1][2][3][4] We previously demonstrated that it is required for optimal in vitro and in vivo growth of Lewis lung carcinoma cells, and our studies suggested that it influences tumor growth via phosphatidylinositol 3 (PI3)-kinase/Akt signaling. 3 It is necessary to elucidate whether or not it plays a crucial role in the growth of both normal and tumor cells not only in culture (where it is a major growth supplement in most growth medium) but also in vivo and especially during the transformation and progression of tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation